Predictive impact of serous retinal detachment in refractory diabetic macular edema - Zhuo-hua Zhou; Lu Zhao; Yan-ling Wang; Jia-lin Wang (BMC Ophthalmology)
Abstract Background Anti-vascular endothelial growth factor (VEGF) drugs are the first-line treatment option for DME management. However, part of DME was refractory to anti-VEGF medicine. With promotion of imaging technology, various retinal morphological characteristics are considered to be related to the prognosis of DME treatment. This study aimed to identify reliable predictive baseline morphological characteristics for refractory diabetic macular edema. Methods This retrospective study was to investigate refractory diabetic macular edema and were followed up for 6 months post-treatment. According to the treatment results, the cohort was divided into refractory or improved group. Baseline morphological characteristics were evaluated and analyzed using optical coherence tomography. Results Serous retinal detachment (63% vs. 25%, P < 0.05) and foveal eversion (77.8% vs. 41.7%, P < 0.05) are more common morphological characteristics in refractory DME than improved group. Binary logistic regression analysis showed average thickness of serous retinal detachment can predict the risk of refractory DME (OR = 1.052, 95% CI 1.005–1.102, P = 0.030). The area under the receiver operating characteristic curves for serous retinal detachment thickness was 0.922 (95% confidence interval 0.713–0.992). Conclusion Patients with refractory diabetic macular edema exhibited an increased incidence of baseline morphological characteristics, including serous retinal detachment and foveal eversion. The thickness of serous retinal detachment can serve as reliable quantitative biomarker, with diabetic macular edema displaying a serous retinal detachment thickness > 162 μm having a potential to become refractory in this study. This finding may promote early detection of refractory diabetic macular edema.